2022
DOI: 10.1097/gox.0000000000004713
|View full text |Cite
|
Sign up to set email alerts
|

Operative Time Predicts Postoperative Outcomes in Bilateral DIEP Flap Reconstruction: Multivariate 1000 Flap Analysis

Abstract: Background: Skin-to-skin operative time (OT) as a risk factor for adverse postoperative outcomes in microvascular breast reconstruction has not been thoroughly investigated. This study evaluates OT’s impact on length of stay (LOS), overall morbidity, individual complications, and unplanned reoperation (UR) in deep inferior epigastric artery perforator (DIEP) flaps, with a primary objective of identifying a clinically relevant time of decreased odds. Methods: Patients who underwent bilateral DIEP flaps from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…readmission treatment (8-10% hourly) compared with the occurrence of any overall postoperative complications (19% hourly) in bilateral DIEP flap breast reconstructions. 4 The risk for overall (25%) and breast flap-site (26%) complications requiring extended hospital stay for treatment was substantially higher per hour of operative time compared with the occurrence of any overall (19%) and breast flap-site (19%) complications in bilateral DIEP flap breast reconstructions, 4 as well as those requiring outpatient or readmission treatment. Increased operative time's disproportionate effect on more severe perioperative complications may be explained by the treatment required to address microvascular issues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…readmission treatment (8-10% hourly) compared with the occurrence of any overall postoperative complications (19% hourly) in bilateral DIEP flap breast reconstructions. 4 The risk for overall (25%) and breast flap-site (26%) complications requiring extended hospital stay for treatment was substantially higher per hour of operative time compared with the occurrence of any overall (19%) and breast flap-site (19%) complications in bilateral DIEP flap breast reconstructions, 4 as well as those requiring outpatient or readmission treatment. Increased operative time's disproportionate effect on more severe perioperative complications may be explained by the treatment required to address microvascular issues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these findings demonstrate that operative time may have a lower impact on the odds of developing less morbid complications only requiring outpatient treatment (9-11% hourly) compared to the occurrence of any overall postoperative complications (19% hourly) in bilateral DIEP flap breast reconstructions. 4 The odds of breast flap-site complications requiring readmission treatment increased by 25% per hour of operative time, while overall and medical complications requiring readmission treatment increased by 8-10% per hour of operative time. In a multicenter study, Mlodinow et al showed that operative time is a predictor of autologous breast reconstruction readmission rates.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…A unilateral DIEP within 8 hours is an acceptable time limit as found by Shammas et al 24 However, with dual consultant operations, operative time can be reduced by nearly an hour and confer increased patient safety. 25 With operative time increasing postoperative complications, 26 surgeons should consider performing more dual consultant operations. Including bilateral cases in our study could be seen to be a counfounding factor for assessing the effect of operative time on odds of donor site morbidity; however, we felt it necessary to include these cases in our analyses to increase the study power.…”
Section: Discussionmentioning
confidence: 99%